2023
DOI: 10.5888/pcd20.220236
|View full text |Cite
|
Sign up to set email alerts
|

Service Availability and Readiness of Primary Care Health Facilities Offering Hypertension Diagnosis Services in Wakiso District, Uganda, 2019

Abstract: What is already known on this topic? Hypertension is the most common cardiovascular disease in the world. If left uncontrolled, it can cause stroke, myocardial infarction, cardiac failure, renal failure, and hypertensive retinopathy. Diagnosis is the first step in managing and treating hypertension. The condition is highly undiagnosed in sub-Saharan Africa because screening programs are limited. What is added by this report?In Uganda, most primary health care facilities offer diagnostic services, but few have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Compared with the results of from other countries, the regional service readiness was both lower and higher than that in other countries. A study from Uganda demonstrated a higher level of service readiness for hypertension management (86%), but with weaknesses in capacity of health staffs and lack of functional equipment [ 19 ]. While another study from Ethiopia reported lower levels of service readiness for Hypertension management at primary health care units (29%), influenced by insufficient equipment for screening and diagnostic, insufficient essential medicines, and lack of basic training and guideline for non-communicable diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the results of from other countries, the regional service readiness was both lower and higher than that in other countries. A study from Uganda demonstrated a higher level of service readiness for hypertension management (86%), but with weaknesses in capacity of health staffs and lack of functional equipment [ 19 ]. While another study from Ethiopia reported lower levels of service readiness for Hypertension management at primary health care units (29%), influenced by insufficient equipment for screening and diagnostic, insufficient essential medicines, and lack of basic training and guideline for non-communicable diseases [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kebijakan kesehatan masyarakat harus mengatasi hipertensi karena merupakan penyebab utama beban penyakit. Intervensi harus terjangkau, berkelanjutan dan efektif (5). Oleh karena itu, program vertikal yang hanya berfokus pada hipertensi tidak disarankan.…”
Section: Pendahuluanunclassified
“…The study specifically focused on service availability, which is defined as the physical presence of the delivery of services, encompassing the health infrastructure, core health personnel, and service utilization [24,26]. The SARA framework is useful in the identification of the proportion of HCFs offering a particular intervention/service-in this case hepatitis B vaccination services, and whether the HCFs offering HBV services met the minimum standards in terms of equipment, trained staff and guidelines, diagnostic capacity, and medicines to provide an adequate level of service (service readiness) [24,27,28]. The data collection tool was reviewed and evaluated for face and internal validity by experts in viral hepatitis research, based at the Makerere University College of Health Sciences.…”
Section: Study Design and Data Collection Toolsmentioning
confidence: 99%